Gambaran Sarana Sanitasi di Asrama Yayasan Pendidikan Islam Pondok Pesantren Ainul Yaqin Kelurahan Lebak Bandung Kecamatan Jelutung Kota Jambi Tahun 2020 - Supriadi Supriadi; Sondang Siahaan; Rina Fauziah (Universitas Batanghari Jambi, 2022)
Sanitation facilities are needed in public places that have the potential for disease transmission, one of which is in Islamic Boarding Schools. Based on the results of a survey at the Ainul Yaqin Islamic Education Foundation, it was found that sanitation facilities did not meet health requirements. The purpose of the study was to obtain an overview of sanitation facilities in the Ainul Yaqin Islamic Education Foundation Dormitory, Lebak Village, Bandung District, Jelutung District, Jambi City. This type of research is descriptive research with an observational approach and research subjects are all sanitation facilities in the dormitory of the Islamic Education Foundation of Pondok Pesantren Ainul Yaqin, Lebak Village, Bandung District, Jelutung District, Jambi City. The results of the study describe the sanitation facilities at the Ainul Yaqin Islamic Education Foundation, showing that the clean water supply facilities in the dormitories meet the requirements, the waste management facilities in the dormitories do not meet the requirements, the human waste disposal facilities in the dormitories meet the requirements, the waste water disposal facilities in the dormitories do not meet the requirements. the requirements and the total score of the overall sanitation facility inspection form did not meet the requirements with a total score of 1398. It was concluded that the sanitation facilities in the dormitory of the Islamic Education Foundation of the Ainul Yaqin Islamic Boarding School in Lebak Bandung Village, Jelutung District, Jambi City did not meet the requirements, it is better to supervise, repair and clean sanitation facilities properly routine.